MEGALITHIC MONUMENTS IN THRISSUR IN HISTORICAL PERSPECTIVE - Valsa .M.A (Rural South Asian Studies, 2015)
Megalithic monuments are the main archaeological findings of Kerala to reinterpret her past history. Prehistoric period can reconstruct with the help of archaeological evidences .Thrissur district is fortunate to have a large number of megalithic sites. Megalithic monuments like Kudakkallu, Toppikkallu, Menhir, Dolmen, Port-holed cist, Stone alignment, Rock-cut caves etc. transfers us to her past. Sifting through Archaeological evidences to reconstruct and reinterpret the history of Kerala during the megalithic period is a challenge that has to be met. This paper makes an attempt to investigate the various types of megalithic monuments in Thrissur district and their historical significance.